2019
DOI: 10.1007/s00380-019-01453-7
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-4 increases with the severity of peripheral arterial disease and is associated with diabetes

Abstract: Thrombospondin-4 (TSP-4) is an extracellular matrix protein of the vessel wall. Despite bench evidence, its significance in the clinical setting of atherosclerosis is missing. TSP-4 (ng/ml) was measured in 365 PAD patientsusing a commercially available ELISA. PAD was diagnosed by the ankle-brachial index (ABI) and clinically graded using the Fontaine classification. TSP-4 levels were significantly higher in Fontaine II vs. Fontaine I (4.78 ± 0. 42, 4.69 ± 0.42, p = 0.043). TSP-4 significantly correlated with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
2
6
0
1
Order By: Relevance
“…MDCF-2 elicits a concerted change in WLZ-associated proteins, a number of which are effectors of bone growth and skeletal muscle development. Some of these proteins have also been implicated in metabolic disorders( 24 30 ). However, augmenting growth of bone and skeletal muscle may promote a rebalancing of the rapid ‘catch-up’ fat accretion, observed when undernourished children are given standard nutritional interventions, towards a more appropriate lean-to-fat mass ratio, simultaneously improving growth and protecting from later obesity( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…MDCF-2 elicits a concerted change in WLZ-associated proteins, a number of which are effectors of bone growth and skeletal muscle development. Some of these proteins have also been implicated in metabolic disorders( 24 30 ). However, augmenting growth of bone and skeletal muscle may promote a rebalancing of the rapid ‘catch-up’ fat accretion, observed when undernourished children are given standard nutritional interventions, towards a more appropriate lean-to-fat mass ratio, simultaneously improving growth and protecting from later obesity( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the rest molecules of the thrombospondin family, TSP-4 promotes angiogenesis (36,37). Recently, Zierfuss et al found increased levels of TSP-4 in T2DM patients with peripheral arterial disease suggesting that microvascular angiogenesis promoted in diabetes is associated with the overexpression of TSP-4 (38).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, serum high mobility group box (HMGB) 1, fibroblast growth factor (FGF) 23 and osteopontin (OPN) have been correlated with the presence of PAD [ 24 , 25 ]. In addition, thrombospondin-4 (TSP-4) levels were significantly increased with PAD severity in patients with concomitant diabetes and could be a novel marker of atherosclerotic activity [ 26 ]. Recently, the association between circulating serum growth differentiation factor (GDF) 15 and lower extremity atherosclerotic disease (LEAD) has been investigated in Chinese diabetes subjects [ 27 ].…”
Section: Discussionmentioning
confidence: 99%